Pulmonary arteriovenous malformation diagnosed by recurrent hemothorax – A case report - Toshiki Sakuma; Hajime Kasai; Toshihiko Sugiura; Kenichiro Takeda; Minori Watanabe; Kenichi Suzuki; Takashi Urushibara; Takuji Suzuki (Respiratory Medicine Case Reports)
Background: A pulmonary arteriovenous malformation (PAVM) is an abnormal connection between a pulmonary artery and vein that causes various complications owing to a right-to-left shunt. However, hemorrhagic complications developing from a PAVM are rare. Case report: We report the case of a 61-year-old woman with a PAVM complicated by hemothorax. She had a history of right hemothorax with no identifiable cause during pregnancy 35 years prior to presentation. Although the PAVM had been identified on chest computed tomography two months previously, the patient was observed. She visited a nearby hospital with back pain and dyspnea without any inciting factor nor history of trauma. Contrast-enhanced chest CT showed a PAVM in the posterior segment of the right upper lobe and another in the apical-posterior segment of the left upper lobe. Detailed examinations suggested both past and present hemothorax due to rupture of the PAVM close to the pleura of the right upper lobe. As there was no progression of the presumed hemothorax during the index hospitalization, the patient was managed conservatively. After the hemothorax resolved, the patient underwent elective coil embolization at our facility. No recurrence of hemothorax was observed over a 10-month follow-up period. Conclusion: A PAVM can cause recurrent hemothorax, and should be considered when evaluating a patient with hemothorax. If the cause of the hemothorax cannot be identified, a PAVM may become apparent after a long period of time.